The impact of tele-expertise in oncology: current state and future perspectives - Heudel, Pierre; Amini-Adle, Mona; Anriot, Julien; Vaz, Gualter; Laine, Claire; Desoutter, Aline; Crochet, Hugo (Frontiers in Digital Health, 2025)
BackgroundTele-expertise, the asynchronous exchange of medical expertise via secured digital platforms, is revolutionizing healthcare delivery. By overcoming geographical and logistical barriers, it enables timely access to specialized care and supports multidisciplinary decision-making, particularly in oncology. Its adoption has accelerated with the COVID-19 pandemic and regulatory changes, improving patient outcomes by facilitating efficient diagnosis and treatment.Materials and methodsAn anaysis of peer-reviewed studies published in the past decade was conducted using PubMed, MEDLINE, and the Cochrane Library. The inclusion criteria focused on studies evaluating tele-expertise for remote consultations, imaging interpretation, pathology evaluation, and multidisciplinary tumor boards. Methodological quality, including study design, sample size, and reliability of outcomes, was assessed. Cross-referencing and manual searches were performed to ensure comprehensive coverage.ResultsThe review demonstrated that tele-expertise improves access to specialized consultations, enhances diagnostic accuracy, and expedites clinical decision-making. Applications in oncology include remote imaging interpretation and support for multidisciplinary teams. Challenges identified include the transmission of large imaging files, the need for secure and robust IT infrastructure, and training healthcare providers. Ethical considerations, such as data privacy and medical liability, remain key barriers.ConclusionTele-expertise is transforming healthcare by enabling equitable access to specialized care and fostering collaboration in oncology. Addressing challenges related to infrastructure, training, and ethical issues is critical to maximizing its potential. The integration of AI and further advancements in telemedicine platforms will enhance its role in delivering high-quality, timely care globally.